A Comprehensive Mathematical Model for Analysis of WR-Resolvers under Stator Short Circuit Fault - H. Lasjerdi; Z. Nasiri-Gheidari; F. Tootoonchian (Journal of Electrical and Computer Engineering Innovations, 2018)
Background and Objectives: Wound-Rotor resolvers are the most widely used position sensors in applications with harsh environmental conditions.Methods the resolver performance is exposed to failure due to the high risk of short circuit (SC) fault. Although the output current of the resolver is negligible, its thin copper wires increase the probability of the short circuit fault. To avoid the propagation of the turn-to-turn SC fault to the whole coil and undesirable performance of the motion control drive, it is necessary to diagnose it at the very beginning of its development. Meanwhile, the first step of diagnosing faults is their modeling. Time stepping finite element analysis is the most accurate, but computationally expensive method for modeling electromagnetic devices. Therefore, it is required to establish an accurate,Results: In this paper, an analytical model based on d-q axes theory is proposed to consider multiple faults, simultaneously. Then, the success of the proposed model is validated by experimental tests on the studied sensor.Conclusion: the proposed model is fast and accurate, so it can be used for the design process.